How to raise an antiracist - Kendi, Ibram X. (One World, an imprint of Random House, 2022)
"The tragedies and reckonings around racism that have rocked the country have created a specific crisis for parents and other caregivers: how do we talk to our children about it? How do we guide our children to avoid repeating our racist history? While we work to dismantle racist behaviors in ourselves and the world around us, how do we raise our children to be antiracists? After he wrote the National Book Award-winning Stamped from the Beginning, readers asked Ibram Kendi, "How can I be antiracist?" After the bestsellers How to Be an Antiracist and Antiracist Baby, readers began asking: "How do I raise an antiracist child?" Dr. Kendi had been pondering the same ever since he became a teacher--but the question became more personal and urgent when he found out his partner, Sadiqa, was pregnant. Like many parents, he didn't know how to answer the question--and wasn't sure he wanted to. He didn't want to educate his child on antiracism; he wanted to shield her from the toxicity of racism altogether. But research and experience helped him realize that antiracism has to be taught and modeled as early as possible--not just to armor our children against the racism still indoctrinated and normalized in their world, but to remind adults to build a more just future for us all. Following the model of his bestselling How to Be an Antiracist, Kendi combines vital scholarship with a compelling personal narrative of his own journey as a parent to create a work whose advice is grounded in research and relatable real-world experience. The chapters follow the stages of child development and don't just help parents to raise antiracists, but also to create an antiracist world for them to grow and thrive in"--